Aqueous garlic extract inhibits protamine sulfate-induced bladder damage - ERCAN, FERİHA; ŞENER, GÖKSEL (KARGER, 2006)
This morphological and biochemical study aims to investigate the antioxidant effects of chronic administration of aqueous garlic extract (AGE) on protamine sulfate (PS)-induced bladder injury. Wistar albino female rats were catheterized and intravesically infused with phosphate-buffered solution (control group) or PS (PS group) dissolved in phosphate-buffered solution. In the PS + AGE group after the PS instillation, AGE (1 ml/kg, i. p., corresponding to 250 mg/kg) was injected intraperitoneally for 3 days. Bladder morphology was investigated by light and scanning electron microscopy. Tissue samples were also obtained to determine bladder malondialdehyde (MDA) and glutathione levels. In the PS group, ulcerated areas, an irregular mucus layer, inflammatory cell infiltration and an increased number of mast cells were observed. In the PS + AGE group a relatively normal urothelial topography, glycosaminoglycan layer and a decreased number of mucosal mast cells and inflammatory cells were observed. Increased MDA levels as a result of PS induction led us to propose that free radicals may have a critical role in this injury. The significant decrease in MDA and increase in glutathione levels in the PS + AGE group was in accordance with morphological findings. Based on the results, AGE treatment significantly prevented PS-induced degenerative morphological and biochemical changes of urinary bladder mucosa. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: aqueous garlic extract; protamine sulfate; urinary bladder; interstitial cystitis; INTERSTITIAL CYSTITIS; OXIDATIVE STRESS; SURFACE GLYCOSAMINOGLYCANS; S-ALLYLCYSTEINE; ANTIOXIDANT; GLUTATHIONE; ATTENUATION; MECHANISMS; PREVENTION; COMPONENTS